11.42 The scottish epilepsy deaths study (SEDS): identifying avoidable epilepsy-related deaths. Issue 12 (14th November 2019) - Mbizvo, Gashirai K; Schnier, Christian; Simpson, Colin R; Chin, Richard FM; Duncan, Susan E
Abstract : Purpose: Quantify avoidable epilepsy-related mortality in adults (aged ≥ 16 years). Method: We identified adult epilepsy-related deaths occurring between 01/01/2009–2016 in Scotland by linking death certificates to administrative primary and secondary care datasets. International Classification of Disease (ICD-10) codes (G40–41, R56.8), Read Codes (F25..), and antiepileptic drugs (AED) were examined in the linked dataset to identify potential epilepsy patients, using clinical data from medical records as a diagnostic reference to calculate positive predictive values (PPV). EPRDs were determined from death certificates (including post-mortem indicators) and medical records, estimating their standardised mortality ratio (SMR) and mortality rate (MR). The Office for National Statistics' Revised Definition of Avoidable Mortality Causes 2016 was used to identify potentially avoidable EPRDs. Results: Combining AED prescription with death certificate epilepsy codes G40–41 had the highest PPV (99%) for epilepsy diagnosis. There were 2, 149 EPRDs. Age-standardised MR per 100, 000 ranged between 6.8 (95%CI 6.0–7.6) in 2009 and 9.1 (95%CI 8.2–9.9) in 2015. SMR was higher in young adults (≤55 years), peaking at 6 (95%CI 2.3–9.7) in the 16–24-year-old group. There were 579 EPRDs in those aged ≤55 years. 31% were SUDEP, 26% respiratory causes (mainly aspiration pneumonias), and 15% mental disorders (mostly alcohol-related). 79% of all EPRDs were potentially avoidable. Commonest modifiable factors were absent epilepsy specialist input, poor patient education, and drug errors. Conclusion: The burden of avoidable epilepsy-related mortality remains high, particularly in young adults.